X=2 and x= -8 x^2+6x-16=0 1) Move the constant (-16) to the right of the equal sign: x^2+6x = 16 (becomes positive) 2) Make the left side a perfect trinomial by doing half of 6 (3) then squaring it (9). Add 9 to the 16: x^2+6x+9= 16+9. 3) Factor the left side, then find the sum of the right side: (x+3)^2 = 25 4) Take the square root of both sides: x+3 =(+/-) 5 (remember it's both positive & negative). The equation will look like x+3= - 5 and x+3=5
5) solve the two equations: x= -8 and x=2
When you put the x-values back into the problem, it should come out 0.
Let's solve your equation step-by-step: x^2+6x-16=0 Factor the left side of the equation:(x-2)(x+8)=0 Set factors equal to 0: x-2=0 or x+8=0, x=2 or x=-8 Your answer is x=2 or x=-8, doesn't matter which, both are correct. Hope this helps!:)